2021
DOI: 10.3389/fmolb.2020.624494
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology-Based Strategies for Berberine Delivery System in Cancer Treatment: Pulling Strings to Keep Berberine in Power

Abstract: Cancer is a multifactorial disease characterized by complex molecular landscape and altered cell pathways that results in an abnormal cell growth. Natural compounds are target-specific and pose a limited cytotoxicity; therefore, can aid in the development of new therapeutic interventions for the treatment of this versatile disease. Berberine is a member of the protoberberine alkaloids family, mainly present in the root, stem, and bark of various trees, and has a reputed anticancer activity. Nonetheless, the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 101 publications
0
28
0
Order By: Relevance
“…Applying the ionic gelation process, berberine-loaded NPs were synthesized for anticancer potential ( 197 ). The rotary evaporated film ultrasonication process was used to create glycyrrhizic acid-loaded NPs ( 198 ).…”
Section: Drug Delivery Systems Entrapping Natural Bioactive Compounds...mentioning
confidence: 99%
“…Applying the ionic gelation process, berberine-loaded NPs were synthesized for anticancer potential ( 197 ). The rotary evaporated film ultrasonication process was used to create glycyrrhizic acid-loaded NPs ( 198 ).…”
Section: Drug Delivery Systems Entrapping Natural Bioactive Compounds...mentioning
confidence: 99%
“…It is the quaternary salt of the isoquinoline alkaloid extracted from many plants, such as Berberis aristata , Berberis aquifolium , Berberis vulgaris , Coptis chinensis , Coptis japonica , and Hydrastis Canadensis [ 2 ]. Many studies have shown the pharmacological actions of BBR including antimicrobial [ 3 4 ], antiviral [ 5 6 ], anti-inflammatory [ 7 ] and antiparasitic effects [ 8 ], and effects against hyperlipidemia [ 9 ], hypoglycemia [ 10 ] and cancer [ 11 ]. BBR has the ability to inhibit or kill many pathogenic bacteria, such as Escherichia coli [ 12 ], Helicobacter pylori [ 13 ], and Staphylococcus aureus , including methicillin-resistant strains and coagulase-negative strains [ 4 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…BBR belongs to the class-III drugs in the biopharmaceutical classification system, indicating that BBR is a lipophilic compound that has poor absorption and low bioavailability [ 24 ]. To improve the effectiveness of BBR, many approaches have been proposed, including synergistic effects with other drugs [ 3 ], particle size reduction [ 25 ], and encapsulation in nanoscale delivery systems [ 11 ]. Nanoscale BBR crystals can be formed using top-down technologies (ball mills, high-pressure homogenizers, microfluidic technology, and spray drying) or bottom-up technologies (evaporative precipitation of nanosuspension (EPN) and antisolvent precipitation (ASP)).…”
Section: Introductionmentioning
confidence: 99%
“…Berberine (BBR) belongs to isoquinoline alkaloids, extracted from various parts like root, rhizome, stem and bark of herbs such as Berberis aristata and Berberis vulgaris. [13][14][15] Active berberine components have shown diversified pharmacological uses, including antilipidemic, anti-depressant and antiinflammatory effects, treatment of diabetics, and control of cardiovascular diseases, anticancer and antimicrobial properties. In the present work, the fabrication of mesoporous magnetic particles was performed using a modified co-precipitation method.…”
Section: Introductionmentioning
confidence: 99%